Big Data Analysis for Strategic Decision Making in Business Information Systems - Tarmizi (Journal Informatic, Education and Management (JIEM), 2023)
The use of big data in the context of strategic decision making in business information systems has become the main focus of research in the current digital era. This research aims to analyze the role of big data in facilitating effective strategic decision making in a rapidly changing business environment. The research methods used include a thorough literature survey and comprehensive analysis of case studies of several leading companies that have adopted big data technology in their business information systems. The research results show that big data has a crucial role in improving strategic decision-making capabilities by providing fast access and in-depth analysis of complex and varied data. This allows organizations to identify market trends, customer behavior patterns and new business opportunities in a more timely and accurate manner. In conclusion, the integration of big data in business information systems is an inevitable strategy for organizations that want to remain competitive in this digital era.